Administrative responsibility of foreign citizens and stateless persons in the Republic of Belarus - Vnuchenkova, Anastasia Yu. (Journal of the Belarusian State University. Law, 2020)
Intensive development of international cooperation, features of the current stage of implementation of state migration policy stimulate the need for the development of migration legislation of the Republic of Belarus. Among the main areas of particular importance is the improvement of legislation regulating the responsibility of foreign citizens and stateless persons for violation of the regime of stay in the Republic of Belarus. Based on the analysis of domestic legislation, scientific literature and statistical data, the author made a conclusion about the need to improve the norms of Belarusian legislation that establish the administrative responsibility of foreign citizens and stateless persons for violating the regime of stay in the Republic of Belarus.